Search for heterotic cross combinations in Indian mustard [Brassica juncea (L.) Czern and Coss]: Search for heterotic cross combinations in Indian mustard [Brassica juncea (L.) Czern and Coss] - KARTIKEYA SRIVASTAVA,; SHIRSAT MAHESH SANTOSH,; GIRISH TANTUWAY,; ADITI ELIZA TIRKEY, (Journal of Oilseeds Research, 2020)
Fifteen indigenous lines of Indian mustard along with three testers namely RH 749, Giriraj and NRCHB 101 were crossed to generate 45 F1s. These hybrids along with their parents were raised in RBD design with 3 replications. The data on the yield and yield traits were taken and analysis of variance, estimation of combining ability effects, heterobeltiosis and economic heterosis followed. Four lines showed positive significant gca effects for number of siliqua/plant while tester Giriraj exhibited positive significant gca effect. IC 571655, IC 571625 and IC558816 displayed highly significant positive gca effect for seed yield/hectare. Giriraj × IC-589670, Giriraj×IC- 571655 and NRCHB-101×IC-558816 displayed positive significant standard heterosis coupled with high per se performance for seed yield/hectare.